Dysbiosis, Host Metabolism, and Non-communicable Diseases: Trialogue in the Inborn Errors of Metabolism - Montanari, Chiara; Parolisi, Sara; Borghi, Elisa; Putignani, Lorenza; Bassanini, Giulia; Zuvadelli, Juri; Bonfanti, Cristina; Tummolo, Albina; Dionisi Vici, Carlo; Biasucci, Giacomo; Burlina, Alberto; Carbone, Maria Teresa; et al. (Frontiers in Physiology, 2021)
Inborn errors of metabolism (IEMs) represent a complex system model, in need of a shift of approach exploring the main factors mediating the regulation of the system, internal or external, and overcoming the traditional concept of biochemical and genetic defects. In this context, among the established factors influencing the metabolic flux, i.e. diet, lifestyle, antibiotics, xenobiotics, infectious agents, also the individual gut microbiota should be considered. Healthy gut microbiota contributes to maintaining human health by providing unique metabolic functions to the human host. Many patients with IEMs are on special diets, the main treatment for these diseases. Hence, IEMs represent a good model to evaluate how specific dietary patterns, in terms of macronutrient composition and quality of nutrients, can be related to a characteristic microbiota associated with a specific clinical phenotype (enterophenotype). In the present review, we aim at reporting the possible links existing between dysbiosis, a condition reported in IEMs patients, and a pro-inflammatory status, through an altered “gut-liver” cross-talk network and major oxidative stress, with a repercussion on the health status of the patient, increasing the risk of Noncommunicable Diseases (NCDs). On this basis, more attention should be paid to the nutritional status assessment and the clinical and biochemical signs of the possible onset of comorbidities, with the goal of improving the long-term wellbeing in IEMs. A balanced intestinal ecosystem has been shown to positively contribute to patient health and its perturbation may influence the clinical spectrum of individuals with IEMs. For this, reaching eubiosis through the improvement of the quality of dietary products and mixtures, the use of pre-, pro- and postbiotics, could represent both a preventive and therapeutic strategy in these complex diseases.